Mimicking effects of auditory verbal hallucinations on language production at the level of words, sentences and stories - Heim, Stefan; Polyak, Stella; Hußmann, Katja (Frontiers in Psychology, 2022)
Schizophrenia is characterised foremost by hallucinations, delusions and disorganised speech. Deficits in the internal speech monitor may contribute to the development of auditory-verbal hallucinations. This study investigates potential effects in the opposite direction: could the presence of auditory-verbal hallucinations have an effect on speech production? To this end, a recent mimicking/simulation approach was adopted for 40 healthy participants who perceived either white noise or hallucination-like speech recordings during different language production tasks with increasing demands: picture naming, verbal fluency with and without category switch, sentence production, and discourse. In line with reports about real schizophrenia cases in the literature, mimicking auditory-verbal hallucinations affected verbal fluency (switch condition) and sentence production (duration) in a different way than mere noise. These effects were not correlated, suggesting that hallucinations may even affect different levels of linguistic complexity in different ways. Anyway, in both cases (mimicked), auditory hallucination appear to contribute to the emergence of disordered speech. The mimicking/simulation paradigm may in future help to identify and disentangle the various factors contributing to disorganised speech in schizophrenia. They may also support the development and implementation of new protocols, e.g., in speech and language therapy in persons with schizophrenia in order to improve their communication skills despite the presence of auditory-verbal hallucinations.